1923
DOI: 10.1001/jama.1923.02650070026009
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Pathologic Physiology of Botulism

Abstract: 4. Pain of Coronary Thrombosis.-Rapid blocking of a large coronary vessel, almost always thrombosis of a sclerosed artery, is accompanied usually by long continued heart pain of very severe nature, not relieved by rest, digitalis or the nitrites, and requiring repeated doses of morphin. The seat of the pain is generally precordial or substernal, but now and then it is abdominal, particularly epigastric, or right or left hypochondrial, and in such instances it is likely to be confused with acute abdominal condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1924
1924
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Botulinum toxin is toxic to all vertebrates through weakening of skeletal muscle, and death may come about through paralysis of the muscles of respiration. Van Ermengen (226) considered that the toxin acted on the central nervous system, but it was later shown that the action is peripheral rather than central (50,60). Most early studies on the mechanism of action of botulinum toxin were carried out with type A crystalline toxin (29,33,79).…”
Section: Microbial Neurotoxins That Block Neurotransmitter Releasementioning
confidence: 99%
“…Botulinum toxin is toxic to all vertebrates through weakening of skeletal muscle, and death may come about through paralysis of the muscles of respiration. Van Ermengen (226) considered that the toxin acted on the central nervous system, but it was later shown that the action is peripheral rather than central (50,60). Most early studies on the mechanism of action of botulinum toxin were carried out with type A crystalline toxin (29,33,79).…”
Section: Microbial Neurotoxins That Block Neurotransmitter Releasementioning
confidence: 99%
“…50. 01, 59 The details of this early work have been reviewed. 177 By 1955 certain salient features of the mechanism and site of action of botulinal toxin had been established.…”
Section: Bacterial Toxins 297mentioning
confidence: 99%
“…The pharmacology of the toxin has been investigated by many workers (for example, Edmunds and Long, 1923;Dickson and Shevky, 1923;Bishop and Bronfenbrenner, 1936;Guyton and MacDonald, 1947), and ithasbeenestablished that the site of action is at the neuromuscular junction. In an investigation of the various factors involved in the paralysis, Burgen, Dickens, and Zatman (1948) utilized the isolated rat phrenic nerve diaphragm preparation of Bulbring (1946).…”
Section: Bacteriological Toxinsmentioning
confidence: 99%